The Influence of Cybersecurity Protection Behavior: Employees of Big Four Account Firm Companies - Hasnul Qalby; Gunawan Yudi Hariyanto; Dyan Tri Utomo; Rano Kartono Rahim (Jurnal Impresi Indonesia, 2025)
This study aims to determine the influence effect of cybersecurity protection behavior from the perspective of employees of Big Four Account Firm Companies. The method used in this research is a quantitative method. The subjects in this study were employees of the Big Four Account Firm with a sample of 150 taken using purposive sampling method. The analysis used in this study was a structural approach to the Equation Model (SEM) by using smart PLS. The results show that Cybersecurity Knowledge has a significant effect towards Self-Efficacy, Cybersecurity Awareness has a significant effect towards Self-Efficacy, and Self-Efficacy has a significant effect towards Cybersecurity Protection Behavior. The managerial implication of this research is important for the organization or management to raise awareness of security culture and can be the reference for other accounting firms.